IMPLICATURE IN SAIKIRAN’S STAND UP COMEDY SCRIPT DARK SKIN AND GETTING MARRIED - Siti Nurhaliza; Zulfan Sahri (Universitas Islam Sumatera Utara, 2021)
This research focuses on implicature in Saikiran’s Stand Up Comedy Script Dark Skin and Getting Married. By using Grice theory of implicature, the make up of this research strongly refers to the use of descriptive qualitative method to process the data, which are originally taken from the script. The analysis reveals two types of implicature i.e. cconventional implicatures and conversational implicatures. Conventional implicature is associated with the general meaning and also related to specific words (but, and, even). Meanwhile, conversational implicature verifies two types, i.e. generalized conversational implicature and particularized conversational implicature. There are 13 data referring to cconventional implicatures and 4 data to conversational implicatures (2 data generalized conversational implicatures and 2 data particularized conversational implicatures). The results of this research indicate that Saikiran uses those implicatures when he wants the audience to understand about his life condition in funny ways, and the audience will possibly find it difficult to understand if they do not know his utterances in the contexts.